Analysis of EDM process parameters on Inconel 718 using the grey-Taguchi and topsis methods - Yuvaraj, Thangavel (Strojniški vestnik, 2019)
Nickel-based superalloys are gaining importance for their growing usage in aerospace industries. Amidst the various advanced machining processes, electro discharge machining (EDM) is considered to be an important one for its ability to machine materials irrespective of its intrinsic properties. In this study, Inconel 718 is considered as a work material, and an L18 orthogonal array (OA) experimental plan is utilized to machine the work material. The influential factors, which affect the EDM performance characteristics, are identified using analysis of variance (ANOVA). Not much work has been done regarding using grey-Taguchi technique for order of preference by similarity to ideal solution (TOPSIS) methods, although these methods can be easily applied for multi-objective optimization. These methods provide the best results with the available sparse data. The best combination of machining factors is determined using grey-Taguchi and TOPSIS methods. Based on the conducted experiments, voltage (V) and pulse off-time (t_off) show a notable contribution on output performance. The optimal combination of input parameter through grey-Taguchi is found to be 10 A, 30 V, 200 %s, and 20 %s respectively, for the EDM parameters: current (I), V, pulse on-time (t_on) and t_off for improved response. Moreover, the best parameter setting (I = 10 A, V = 30 V, t_on =100 %s and t_off = 20 %s) is identified using the TOPSIS method for the performance measures machining rate (MR), tool wear rate (TWR), overcut (OC), and taper overcut (TOC). Further tool wear behaviour is also studied through scanning electron microscope (SEM) images by varying the voltage.
Keywords: ANOVA; grey-Taguchi; Inconel; konusi; nadmera; overcut; taper; TOPSIS